Intratumoral STING activation causes durable immunogenic tumor eradication in the KP soft tissue sarcoma model - Marritt, Kayla L.; Hildebrand, Karys M.; Hildebrand, Kurt N.; Singla, Arvind K.; Zemp, Franz J.; Mahoney, Douglas J.; Jirik, Frank R.; Monument, Michael J. (Frontiers in Immunology, 2023)
Soft tissue sarcomas (STS) are highly metastatic, connective-tissue lineage solid cancers. Immunologically, sarcomas are frequently characterized by a paucity of tumor infiltrating lymphocytes and an immune suppressive microenvironment. Activation of the STING pathway can induce potent immune-driven anti-tumor responses within immunogenic solid tumors; however, this strategy has not been evaluated in immunologically cold sarcomas. Herein, we assessed the therapeutic response of intratumoral STING activation in an immunologically cold murine model of undifferentiated pleomorphic sarcoma (UPS). A single intratumoral injection of the murine STING agonist, DMXAA resulted in durable cure in up to 60% of UPS-bearing mice. In mice with synchronous lung metastases, STING activation within hindlimb tumors resulted in 50% cure in both anatomic sites. Surviving mice all rejected UPS re-challenge in the hindlimb and lung. Therapeutic efficacy of STING was inhibited by lymphocyte deficiency but unaffected by macrophage deficiency. Immune phenotyping demonstrated enrichment of lymphocytic responses in tumors at multiple timepoints following treatment. Immune checkpoint blockade enhanced survival following STING activation. These data suggest intratumoral activation of the STING pathway elicits local and systemic anti-tumor immune responses in a lymphocyte poor sarcoma model and deserves further evaluation as an adjunctive local and systemic treatment for sarcomas.